2017
DOI: 10.5455/jice.20170411091159
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of herbal volatile oil extracts against multidrug resistant Acinetobacter baumannii

Abstract: Aim:The aim of the study is to investigate the antibacterial activity of 10 volatile oils extracted from medicinal plants, including galangal (Alpinia galanga Linn.), ginger (Zingiber officinale), plai (Zingiber cassumunar Roxb.), lime (Citrus aurantifolia), kaffir lime (Citrus hystrix DC.), sweet basil (Ocimum basilicum Linn.), tree basil (Ocimum gratissimum), lemongrass (Cymbopogon citratus DC.), clove (Syzygium aromaticum), and cinnamon (Cinnamomum verum) against four standard strains of Staphylococcus aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 24 publications
3
24
0
1
Order By: Relevance
“…The corresponding MBC were 4 mg/ml. Tea tree oil was used as positive control in this study with MIC and MBC values of 2 and 4 mg/ml, respectively [30]. The antifungal activity of Vietnamese ginger essential oil with ar-cucumene, β-bisabolene, α-zingiberene and β-sesquiphellandrene against Botrytis cinerea, Penicillium sp., Aspergillus niger, followed by Rhizopus nigricans, Saccharomyces cerevisiae, and Candida albicans, were confirmed.…”
Section: Antimicrobial Activity Of Ginger Essential Oilmentioning
confidence: 99%
“…The corresponding MBC were 4 mg/ml. Tea tree oil was used as positive control in this study with MIC and MBC values of 2 and 4 mg/ml, respectively [30]. The antifungal activity of Vietnamese ginger essential oil with ar-cucumene, β-bisabolene, α-zingiberene and β-sesquiphellandrene against Botrytis cinerea, Penicillium sp., Aspergillus niger, followed by Rhizopus nigricans, Saccharomyces cerevisiae, and Candida albicans, were confirmed.…”
Section: Antimicrobial Activity Of Ginger Essential Oilmentioning
confidence: 99%
“…For instance, Miyasaki et al (42) showed that most of the de-tanninized parts of the Scutellaria baicalensis have a good effect against these bacteria (MIC 90 = 128 µg/mL). Karaman et al (43) also demonstrated that the methanolic extract of Juniperus oxycedrus L. has a good effect against A. Baumannii and (44) found that the extracts of Cinnamomum verum, Syzygium aromaticum, and Ocimumbasilicum Linn. volatile oils had an effective minimum bactericidal concentration against A. baumannii (MBC 90 = 0.5, 1, and 2 µg/mL, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…500 grams of peel distilled for 4 hours and dried over anhydrous sodium sulfate gave 0.97% of kaffir lime oil with β‐pinene (30.48%), sabinene (22.75%), and citronellal (15.66%) being the major components 30 . Similarly, 3‐5 hours of hydrodistillation obtained 2.1% yield 31 . Hydrodistillation with 500 gram of peel for 4 hours using simple quick‐fit apparatus dried over anhydrous sodium sulfate resulted in production yield of 0.77% with 19 compounds majorly citronellol (10.67%), limonene (7.32%), linalool (5.83%), and o‐cymene (5.51%) 32 …”
Section: Methods Of Kaffir Lime Oil Extractionmentioning
confidence: 99%
“…Essential oil extracted from kaffir lime was revealed to contain a complex mixture of bioactive compounds that possess biological activities including antimicrobial 30,31,47,67‐69 and antioxidant activities 8,34 . Srisukh et al 70 reported kaffir lime oil to exhibit antibacterial activity against 411 isolates from patients suffering from respiratory tract infections.…”
Section: Application Of Kaffir Lime Oilmentioning
confidence: 99%